2018
DOI: 10.3390/fermentation5010004
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Bioethanol Production: On the Use of Pulp and Paper Industry Wastes as Feedstock

Abstract: Due to the health and environment impacts of fossil fuels utilization, biofuels have been investigated as a potential alternative renewable source of energy. Bioethanol is currently the most produced biofuel, mainly of first generation, resulting in food-fuel competition. Second generation bioethanol is produced from lignocellulosic biomass, but a costly and difficult pretreatment is required. The pulp and paper industry has the biggest income of biomass for non-food-chain production, and, simultaneously gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
120
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 188 publications
(296 reference statements)
0
120
0
4
Order By: Relevance
“…The release of enzymatic and fermentation inhibitors during pretreatment is another limitation [9].Pulp and paper mills have the infrastructures and logistics to handle LCB, and chemical mills employ technology required for LCB fractionation and conversion [10]. Bioethanol has been produced from different feedstocks such as Kraft pulp, spent sulfite liquor, and pulp and paper sludge [11]. Chemical pulping processes can be considered as a LCB pretreatment since they promote delignification and target hemicelluloses to some degree [12].…”
mentioning
confidence: 99%
“…The release of enzymatic and fermentation inhibitors during pretreatment is another limitation [9].Pulp and paper mills have the infrastructures and logistics to handle LCB, and chemical mills employ technology required for LCB fractionation and conversion [10]. Bioethanol has been produced from different feedstocks such as Kraft pulp, spent sulfite liquor, and pulp and paper sludge [11]. Chemical pulping processes can be considered as a LCB pretreatment since they promote delignification and target hemicelluloses to some degree [12].…”
mentioning
confidence: 99%
“…Although there is no exact data on the accessibility of agricultural waste, the amount could be estimated using the ratio between crop and residual production whereby 10 tons of corn grain produced (with 15% moisture content) could generate 8.5 tons of dried corn stover . As there is no rivalry for land, bioethanol production from agricultural waste should have a minimal impact on the rise of food price …”
Section: Prospective Of Secondary Bioethanol Productionmentioning
confidence: 99%
“…24 As there is no rivalry for land, bioethanol production from agricultural waste should have a minimal impact on the rise of food price. 7 Besides, a convincing adaptability of cellulosic ethanol as an additive to fuel could be justified with octane rating. It was reported that 25-40% of ethanol blended gasoline could boost the octane number and eventually increase the efficiency of engine.…”
Section: Prospective Of Secondary Bioethanol Productionmentioning
confidence: 99%
See 2 more Smart Citations